Historical abiotic events or human‐aided dispersal: inferring the evolutionary history of a newly discovered galaxiid fish. Issue 7 (4th March 2015) - Chakona, Gamuchirai; Swartz, Ernst R.; Chakona, Albert
Abstract Range expansion of obligate freshwater fishes in the Cape Floristic Region (CFR) of South Africa has mostly been attributed to river capture events and confluence of rivers following sea‐level regression. The role of low drainage divides and interbasin water transfers has received less attention. This study analyzed mitochondrial and nuclear DNA sequences to assess the processes that could have influenced the phylogeographic patterns of a newly discovered lineage of Galaxias zebratus (hereafter Galaxias zebratus "Joubertina") that occurs across two currently isolated river systems close to the Joubertina area in the eastern CFR. Results from both analyses revealed that observed genetic differentiation cannot be explained by isolation between the two river systems. No genetic differentiation was found between the Krom River system and a population from one of the Gamtoos tributaries. Shallow genetic differentiation was found between the Krom and the other Gamtoos populations. Historical river capture events and sea‐level changes do not explain the present distribution of Galaxias zebratus "Joubertina" across the Krom and Gamtoos River systems. Interbasin dispersal during pluvial periods, recent river capture, or recent human‐mediated translocation seems to be the most plausible explanations.